2007
DOI: 10.2174/156802607779318244
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in α1-Adrenoreceptor Antagonists as Pharmacological Tools and Therapeutic Agents

Abstract: Native alpha(1)-adrenoreceptors (ARs) appear to exist as three different subtypes encoded by three genes, alpha(1A/1a), alpha(1B/1b), and alpha(1D/1d). Historically, the discovery of agents selective for each of the three alpha(1)-AR subtypes has been an active area of medicinal chemistry research because of the wide number of possible therapeutic applications. Initially introduced for the management of hypertension, alpha(1)-AR antagonists have, in fact, become increasingly common in the treatment of benign p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…However, a possible limitation in the novel application of adrenoceptor antagonists in cancer treatment is their side effects notably caused by smooth muscle relaxation, resulting in cardiovascular-associated hypotension [34]. But in the case of alpha antagonists, new tissue-specific versions are being engineered to give fewer side effects [14,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a possible limitation in the novel application of adrenoceptor antagonists in cancer treatment is their side effects notably caused by smooth muscle relaxation, resulting in cardiovascular-associated hypotension [34]. But in the case of alpha antagonists, new tissue-specific versions are being engineered to give fewer side effects [14,35].…”
Section: Discussionmentioning
confidence: 99%
“…Adrenoceptor antagonists comprise two main groups, alpha-and beta-receptor-specific antagonists [13,14], and have recently received attention for offering a novel therapeutic approach in the treatment of cancer. One such study showed coincidental treatment with a1-adrenoceptor antagonists (doxazosin and terazosin) for hypertension or benign prostate hyperplasia significantly lowered the incidence of prostate cancer [15].…”
mentioning
confidence: 99%
“…Multiple subtypes of α 1 -adrenoceptors have been identified in vascular tissues and are named α 1A -, α 1B -, and α 1Dadrenoceptors [1][2][3][4][5][6][7] . An RNAse protection assay showed that the main renal arteries and branches of renal arteries have mRNA encoding α 1A -adrenoceptors in much greater proportions than those encoding α 1B -and α 1D -adrenoceptor subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…The aggressive pursuit of the expression profile, subtype characterization, cellular localization, pharmacological characteristics, structure and function of the α1-AR subtypes, established an ideal molecular platform for the discovery and development of a large number of subtype selective antagonists that impacted clinical care and therapeutic approaches of various conditions, primarily, benign prostate hyperplasia/bladder outlet obstruction and hypertension [46]. The existence of multiple α1-AR subtypes points out the need of developing new molecules, which target only one receptor while not affecting others localized at different sites.…”
Section: Discussionmentioning
confidence: 99%
“…Quinazoline bearing compounds are in general typified by Prazosin, and the 2,4-diamino-6,7-dimethoxyquinazoline moiety is considered as analogue of noradrenaline, where a dominant role in the AR recognition process is played by the protonated N1 of the moiety which mimics the amine function of the neurotransmitter, protonated at physiological pH [46]. The different localization of AR subtypes accelerated the possibility of designing drugs that selectively interact with distinct AR subtypes, thus avoiding the occurrence of possible side effects in other organs.…”
Section: Therapeutic Targeting Of Adrenoceptorsmentioning
confidence: 99%